ALGORITHM OF DIAGNOSIS AND TREATMENT OF PATIENTS WITH PELVIC TRAUMA COMPLICATED WITH RETROPERITONEAL HEMORRHAGE - A. M. Fayn; A. N. Smolyar; P. A. Ivanov; N. N. Zadneprovskiy (Неотложная медицинская помощь, 2017)
Introduction. Despite great diagnostic and therapeutic advances, the amount of complications and mortality rate in patients with retroperitoneal hemorrhage associated with pelvic trauma remains high. The primary aim of treatment in such patients is early recognition and arrest of bleeding source and intensive therapy. Thus, the development of diagnostic and treatment algorithm is important for improvement the results of treatment of patients with pelvic trauma complicated by retroperitoneal hemorrhage.The aim of the study is to evaluate the effectiveness of the developed algorithm for diagnosis and treatment of patients with pelvic trauma complicated with retroperitoneal hemorrhage.Material and Methods. Retrospective comparative analysis was performed in 374 patients with pelvic fractures complicated with retroperitoneal hemorrhage who were admitted to our hospital from 2007 to 2015. The study group consisted of 164 patients who were treated according to the new algorithm for diagnosis and treatment. The control group consisted of 210 patients who were not treated with the developed algorithm.Results. Clinical use of the developed algorithm led to reduction in mortality from 12.2 to 9.7%. The number of common complications decreased from 41.3 to 25.0%, and local complications decreased from 28.6 to 18.9%. The time of patients’ activation after the definitive fixation of pelvis reduced from 17.5 to 7.6 days. The average hospital stay decreased from 46.1 to 35.2 days.Conclusion. The developed diagnostic and treatment algorithm helped reduce mortality rate, the number of general and local complications in patients with pelvic trauma complicated by retroperitoneal hemorrhage as well as the duration of bed rest and hospital stay.